Entrepreneurial Mindset Development through Curriculum and Infrastructure Requirements towards the Making of Developed India: Issues and Challenges - Tripathi, Hitesh; Johri, Gyanendra B. S.; Srivastava, Pradeep Kumar; Srivastava, Sharad (Journal of Business and Management, 2025)
Background: Entrepreneurial mindset development is increasingly considered essential in higher education to foster students' innovation, self-reliance, and economic resilience. However, traditional academic curricula often fall short in promoting such skills.Objectives: This study explores how an academic curriculum can be effectively designed to foster the development of an entrepreneurial mindset in students.Methods: A pilot study was conducted using a structured online questionnaire administered to academicians, students, and entrepreneurs across various domains. Exploratory Factor Analysis (EFA) uncovered underlying relationships between curriculum elements and entrepreneurial mindset development.Results: Two key factors emerged from the EFA: (1) thematic theory, including classroom lectures and practical sessions, and (2) the establishment of an Entrepreneurship Development Cell (EDC) to support experiential learning. These elements were found to be instrumental in fostering entrepreneurial thinking.Conclusion: The findings highlight the need for a paradigm shift in academic environments, emphasizing entrepreneurial actions over conventional pedagogies. Strengthening collaboration between academic, industry, and local communities is crucial. The study recommends embedding entrepreneurship into the university curriculum to cultivate independence and innovation among students, while future research should further identify additional cognitive and structural factors influencing mindset development.JEL Classification: Z130, Z150, Z190